Apakah Terjadi Perpindahan Simpanan Nasabah Bank Kecil Ke Bank Besar (Flight to Quality) Pada Saat Krisis Pandemi Covid-19? - Hasan Ashari; Trinandari Prasetyo Nugrahanti (Akuntabilitas, 2021)
This paper aims to explain whether flight to quality or the transfer of deposit funds from small banks to large banks actually occurred during the Covid-19 pandemic crisis as suspected by banking analysts. This research is descriptive research with a quantitative approach. The secondary data source in this study was obtained from the website of the Indonesia Deposit Insurance Corporation which lists the value of Commercial Bank Deposits from July 2013 to d. July 2020. Analysis of the data using panel data regression analysis. The results of this study conclude that 1) the Covid-19 pandemic does not significantly affect the performance of small banks in collecting deposits, 2) the Covid-19 pandemic causes flight to quality small bank deposits, namely Book 1 banks, Islamic banks, and regional banks to category banks. others who have large assets and 3) Economic growth does not affect the performance of small banks in collecting deposits during the Covid-19 Pandemic.How to Cite:Ashari, H., & Nugrahanti, T. P. (2021). Apakah Terjadi Perpindahan Simpanan Nasabah Bank Kecil ke Bank Besar (Flight to Quality) Pada Saat Krisis Pandemi Covid-19? Akuntabilitas: Jurnal Ilmu Akuntansi, 14(2), 215-230.